Pore and fracture development in coal under stress conditions based on nuclear magnetic resonance and fractal theory. (1st February 2022) - Zhao, Yu; Wang, Chaolin; Ning, Lin; Zhao, Houfa; Bi, Jing
Highlights: Pore evolution in coal during loading was investigated based on NMR measurement. Characteristics of T2 distribution and pores in coals were analyzed during loading. NMR fractal dimensions of stress-damaged coal were measured. Abstract: In this paper, triaxial compression tests on coals with real-time T2 and MRI (Magnetic Resonance Imaging) image measurement are performed by using a nuclear magnetic resonance (NMR) testing system equipped with a loading device. Pore and fracture development in coal under stress conditions are investigated based on NMR and fractal theory. The results show that the accumulation of NMR signal intensity as well as sample porosity decrease slightly at first, then increase slowly, and finally increase rapidly during the deformation of coal. The measured T2 distributions indicate that stress damage mainly induces the generation of mesopores and macropores (or micro-fractures). A new method for estimating crack-initiation stresses is proposed based on the evolution of T2 curve. By using this method, we estimate the crack-initiation stress of the tested coal samples, which is 34.6%, 32.2%, and 30.1% of its corresponding peak strength, respectively. Fractal dimensions of seepage pores show significant fractal characteristics, while fractal characteristics of adsorption pores are not obvious. The evolution of fractal dimension DT of the total pores with stress is similar to the changing trend of porosity. But the fractal dimension of DS shows a negative correlation with the stress.